2023
DOI: 10.1002/hsr2.1069
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox and sex: Sexual orientations and encounters are key factors to consider

Abstract: Background and Aims The monkeypox (mpox) virus was endemic to some African countries that have recently spread worldwide creating multicountry outbreaks outside of Africa. This most current mpox outbreak is caused by a variety of factors. However, there are some conflicting ideas and pejorative claims about this. Therefore, we conducted this narrative review to highlight the associations of mpox infection with sexual orientations and encounters and to break the misconception about mpox. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
(97 reference statements)
0
11
0
7
Order By: Relevance
“…The score of PLWH with a fixed sexual partner is higher than that with out a fixed sexual partner, and the difference is statistically significant (P<0.01). There is limited research on the correlation between sexual orientation, fixed sexual partner and monkeypox prevention behavior, but previous studies have confirmed a significant correlation between sexual orientation, fixed sexual partner and monkeypox infection [39]. Every PLWH has received ART related treatment and doesn't infect with monkeypox ever or currently.…”
Section: Model Analysis Resultsmentioning
confidence: 99%
“…The score of PLWH with a fixed sexual partner is higher than that with out a fixed sexual partner, and the difference is statistically significant (P<0.01). There is limited research on the correlation between sexual orientation, fixed sexual partner and monkeypox prevention behavior, but previous studies have confirmed a significant correlation between sexual orientation, fixed sexual partner and monkeypox infection [39]. Every PLWH has received ART related treatment and doesn't infect with monkeypox ever or currently.…”
Section: Model Analysis Resultsmentioning
confidence: 99%
“…The likelihood of having high subjective norms was 2. 25 higher in people having one sexual partner than those involved with more than one sexual partner.…”
Section: Regression Analysismentioning
confidence: 89%
“… 19 , 20 , 21 , 22 , 23 , 24 So, individual risk perception and subjective norms are critical predictors of vaccination decisions against Mpox. Since the current Mpox disease is more likely to affect young, middle‐aged males, 25 , 26 it is essential to know about their perception of risk and subjective norms related to Mpox, which would provide insight into their decision on vaccination if in future any vaccination program against Mpox infection is recommended. Therefore, we aimed to conduct this cross‐sectional survey on the male population to assess their risk perceptions and subjective norms, which will considerably contribute to combating this new emerging threat.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients were men who had sex with men and some had heterosexual contacts. [3] Rarely did we come across with patients without any sexual contact. Interestingly, we have noticed that the incidence of this disease is low in females.…”
Section: Article In Pressmentioning
confidence: 99%